2010
DOI: 10.1002/anie.201002033
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Sixth DNA Base Hydroxymethylcytosine in the Brain

Abstract: Mind over matter: LC‐MS has allowed the amount of the post‐replicatively formed DNA base 5‐hydroxymethylcytosine (see picture; left) to be quantified in brain tissue. The nucleoside is most abundant in areas that are associated with higher cognitive functions, and its content in mouse hippocampi seems to increase with age. The new method enables hydroxymethylcytosine to be quantified with unprecedented accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
272
0
21

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(321 citation statements)
references
References 25 publications
20
272
0
21
Order By: Relevance
“…Further, the relationship between CpG methylation and transcription is not linear with transcription beginning at times before it is demethylated (Buschhausen et al, 1985;Sharma et al, 2010). Finally, recent studies indicate that 5HMC accounts for 14% of the methylcytosines in the brain Munzel et al, 2010). Most previous DNA methylation studies of clinical populations used methods incapable of distinguishing 5MC from 5HMC.…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 98%
“…Further, the relationship between CpG methylation and transcription is not linear with transcription beginning at times before it is demethylated (Buschhausen et al, 1985;Sharma et al, 2010). Finally, recent studies indicate that 5HMC accounts for 14% of the methylcytosines in the brain Munzel et al, 2010). Most previous DNA methylation studies of clinical populations used methods incapable of distinguishing 5MC from 5HMC.…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 98%
“…[23][24][25][26][27] This discovery did not attract significant attention until 2009, when two laboratories independently reported the groundbreaking (re)discovery of 5hmCs in mammalian genomic DNA. In one study, Kriaucionic and Heintz used an elegant genetic labeling approach to purify nuclei from two distinct neuronal subtypes from the mouse cerebellum.…”
Section: Discovery Of the Tet Proteins And 5hmcsmentioning
confidence: 99%
“…Following these two studies, many other laboratories have confirmed and extended these results using various methods. [24][25][26][27]30,31 5hmC as an Intermediate of Active DNA Demethylation: Indirect Evidence…”
mentioning
confidence: 99%
“…LC/MS delivers specificity by monitoring selected mass ion transitions and extreme sensitivity by enhanced signal-to-noise ratio. LC/MS has been successfully used to detect and quantify 5hmC, 5fC and 5caC in mouse embryonic stem cells (ESCs) and mammalian tissues [5,9,10,16,17,[24][25][26].…”
Section: Global Detection and Quantification Of Nucleoside Variants: mentioning
confidence: 99%
“…Isotopelabelled standards can be spiked into the samples to provide an internal control [24,25]; the isotope-labelled "heavy" standard will be affected the same way as its "light" counterpart and thus can be used to monitor the loss/gain of signal caused by ion suppression. This technique has been used to accurately quantify 5hmC in different parts of the brain, confirming 5hmC as a new post-replicative mark [25].…”
Section: Global Detection and Quantification Of Nucleoside Variants: mentioning
confidence: 99%